Verbal Expressions of Refusing and Begging of 4,9 to 5,1 Years Old Boy: Case Study of Muhammad Zaini - Muhammad Rafiek (Kandai, 2018)
This research aims to describe and explain about verbal expression of refusing and begging (pitiful) on Muhammad Zaini, a boy aged 4 years 9 months to 5 years 1 month. The method used in this research is qualitative method with based language acquisition of children. Data were analyzed by applying longitudinal techniques.The result of this research shows that there are verbal expressions for refusing on Muhammad Zaini who set in Banjar people, such as “indah” (not or don't want to), jangan (do not), eh ... ehm, “kada” (not), “lain” (not), and the expression of pain.In addition also the verbal expression is found begging (pitiful) on Muhammad Zaini in the form of greeting ”jangan sarik”(do not get angry),“ulun indah disariki” (I don't want to get yelled at), jangan (do not), and ask something.